Inflamação, apolipoproteínas e diurese residual em pacientes com doença renal crônica em hemodiálise: um estudo observacional - Borges, Daniela Lemos (2014)
Introduction: Residual diuresis (RD) is the simplest method for measuring renal residual function in patients with chronic kidney disease (CKD). A reduction in RD is associated with intensification of the inflammatory process caused by uremia. However, little is known regarding the relation between RD and inflammatory markers in these patients. We verify possible associations among the inflammatory state, atherogenic factors, and RD, in patients with CKD undergoing hemodialysis. Methods: This study enrolled 80 patients with CKD undergoing hemodialysis. Patients were stratified according to RD: the anuric (RD-) group, whose collected urinary volume was ≤ 100 mL/24 h (n = 47); and the non-anuric (RD+) group, whose urinary volume was >100 mL/24 h (n = 33). Demographic information, comorbidity, use of medication, anthropometric data, and blood pressure were analyzed. Serum high-sensitivity C-reactive protein (hs-CRP), and apolipoprotein (Apo) AI and B levels were measured after fasting for 12 h. Urine volumes were collected in a 24 h period during the interdialytic period. Results: Serum hs-CRP levels were higher in the RD- group than in the RD+ group (P = 0.015). In the total group, hs-CRP was significantly correlated with RD (r= −0.25, P = 0.025) and Apo AI (r= −0.25, P = 0.024). A greater proportion of patients had reduced plasma concentrations of Apo AI in the RD- group (31.9%) compared with the RD+ group (9.1%) (P = 0.014). Conclusion: There are relations among a reduction in RD, inflammatory state, and a reduction in Apo AI levels in patients with CKD. Apo AI plays a role in predicting development of inflammatory processes. There is no association of Apo B with hs-CRP or RD.